Autocuidado presente en estudiantes de enfermería de la Universidad de Sonora - Ortega-Falcón, Mariana del Rosario (Universidad de Sonora, 2019)
Self-care refers to the practice of activities that individuals initiate and perform to their advantage to maintain life, health and welfare. The future health professionals should be able to make a positive change in people, therefore must possess a self-care in their daily work, enabling them to live healthily and be on welfare to care for others, fulfilling the role of model and educator. This study aimed to meet self-care practices of students in the Bachelor of Nursing third semester at the University of Sonora, Central Campus. Quantitative, descriptive, prospective and transversal study. With a sample of 100 students of Nursing. Self-care of this sample resulted in a regular level. Minor self-care practices were found in the areas of sleep, rest, nutrition, physical activity, and lack of regular review of preventive health. Conclusion: The University of Sonora in conjunction with the Department of Nursing can contribute actively to improve the level of self care youth through programs that promote healthy practices.